Assessment of Irisin and Nesfatin-1 Levels in Non-Obese and Obese Women with Polycystic Ovarian Syndrome - Ali Al-Sajaad Mohammed Al-Azzawi; Hiba Resheed Behayaa; Ban Aamer Mousa (Medical Journal of Babylon, 2025)
Background: In the developed world, some of the most common ovarian disorders include polycystic ovarian syndrome (PCOS), ovulatory dysfunction, hyperandrogenism, and polycystic ovaries which are the most characteristic in this woman endocrinopathy. It is associated with hyperinsulinemia and metabolic disorder. Objective: To estimate irisin, nesfatin-,1 and other biochemical parameters in obese and non-obese women with PCOS. Materials and Methods: The study comprised 90 women aged between 18 and 40 years, divided into two sub-groups. The first group consisted of 45 obese women with PCOS, and the second group consisted of 45 non-obese women with PCOS. Smokers, women with hypertension, or women consuming oral contraceptives were excluded from the groups. To determine whether the women were obese or not, body mass index was used. Results: The results of the study revealed that obese women with PCOS showed significantly higher levels of BMI, irisin, nesfatin-1, insulin, fasting glucose, and HOMA-IR compared to non-obese women (P ≤ 0.05). However, no significant differences were found in LH, FSH, LH/FSH ratio, and total testosterone between the groups (P < 0.05). Conclusion: Irisin and nesfatin-1 levels surged in women with PCOS make them critical biomarkers in the progress of PCOS in obese and non-obese women.